First person - Siobhan Crilly (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Siobhan Crilly is first author on ' Zebrafish drug screening identifies candidate therapies for neuroprotection after spontaneous intracerebral haemorrhage', published in DMM. Siobhan conducted the research described in this article while a postdoctoral research associate in Paul Kasher's lab at The University of Manchester, Manchester, UK. She is now an NC3Rs training fellow in the lab of Paul Kasher and Annalisa Tirella at The University of Manchester, investigating haemorrhagic stroke modelling.